Management of Meige syndrome with bilateral trigeminal and facial nerves combing - Tingting Ying; Tingting Ying; Haopeng Wang; Haopeng Wang; Yinda Tang; Yinda Tang; Hua Zhao; Hua Zhao; Xiaomin Cai; Xiaomin Cai; Yiman Shen; Yiman Shen; et al. (Frontiers in Neurology, 2024)
ObjectiveMeige syndrome (MS) is an adult-onset segmental dystonia for which no satisfactory remedy currently exists. Our team developed a novel surgical approach called bilateral trigeminal/facial nerve combing (BTFC). This study aimed to evaluate the outcomes of patients who underwent BFTC (Clinical Trial Registry Number: ChiCTR2000033481).MethodWe assigned 22 patients with MS to undergo BTFC. The primary outcome was assessed using the movement subscale of the Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS-M) at 12 months postoperatively. The second outcome was evaluated using the Medical Outcome Study (MOS) 36-item Short Form Health Survey (SF-36), the dysfunction subscale of the Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS-D), and the sub-item scores of the BFMDRS-M. Safety outcomes included the House-Brackmann (HB) functional grading score and the visual analog scale (VAS) for facial numbness.ResultsAt the final follow-up at 12 months, the BFMDRS-M showed a mean improvement of 70.7% from baseline. Mean scores of the BFMDRS-M sub-motor (including the eyes, mouth, and speech/swallowing) improved by 65.6, 81.00, and 60%, respectively. The median score of the total BFMDRS-D score was 0.70 ± 1.17 compared with 1.86 ± 2.21 at baseline. There were no serious operative complications in this population. The quality of life of the patients significantly improved (P < 0.05).ConclusionBFTC has proven to be effective in relieving the symptoms of Meige syndrome. This novel surgical approach offers a new alternative treatment for patients who have failed to respond to medications, botulinum toxin injections, and deep brain stimulation (DBS).Clinical Trial Registrationhttps://www.chictr.org.cn/bin/project/edit?pid=54567, ChiCTR2000033481.